2012
DOI: 10.1002/met.1322
|View full text |Cite
|
Sign up to set email alerts
|

Northeast monsoon over India: variability and prediction

Abstract: South peninsular India experiences a large portion of the annual rainfall during the northeast monsoon season (October to December). In this study, the facets of diurnal, intra-seasonal and inter-annual variability of the northeast monsoon rainfall (the NEMR) over India have been examined. The analysis of satellite derived hourly rainfall reveals that there are distinct features of diurnal variation over the land and oceans during the season. Over the land, rainfall peaks during the late afternoon/evening, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 38 publications
4
164
0
Order By: Relevance
“…Far less effort has focused on pre-and postmonsoon precipitation in spite of its importance to water resources, agriculture, and livelihoods in the northwestern/Himalayan and southern peninsular regions of the subcontinent (Immerzeel et al 2009;Bookhagen and Burbank 2010). The magnitude and mechanistic explanation of precipitation and its variability during these seasons and/or regions remains unclear and poorly investigated (Kripalani and Kumar 2004;Sen Roy 2006;Rajeevan et al 2012;Kar and Rana 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Far less effort has focused on pre-and postmonsoon precipitation in spite of its importance to water resources, agriculture, and livelihoods in the northwestern/Himalayan and southern peninsular regions of the subcontinent (Immerzeel et al 2009;Bookhagen and Burbank 2010). The magnitude and mechanistic explanation of precipitation and its variability during these seasons and/or regions remains unclear and poorly investigated (Kripalani and Kumar 2004;Sen Roy 2006;Rajeevan et al 2012;Kar and Rana 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The positive vorticity during the wet conditions shifted northwards from the seasonal climatology and the center of positive anomaly located over the southeastern peninsular India (see Figures (a) and (d)). The northward movement of cyclonic circulation during the State‐1 was consistent with the northward propagation of rainfall episodes during the NEIMR period (Rajeevan et al, ). These physical processes could result in the wet NEIMR condition observed over the southeastern peninsular India.…”
Section: Discussionmentioning
confidence: 99%
“…As Charlotte et al () highlighted, it was not simple to correlate the identified prominent variations in seasonal NEIMR to intra‐seasonal NEIMR. Therefore, extensive research is required to understand the intra‐seasonal nature of NEIMR (Charlotte et al, ; Rajeevan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The SW and NE monsoon were studied separately by many researchers viz. Pai (2004), Rajeevan et al (2012), Balachandran et al (2006) etc. The excess or deficit SW monsoon rainfall is negatively correlated with NE monsoon rainfall (Dhar and Rakhecha, 1983;Selvaraj and Aditya, 2011).…”
Section: Introductionmentioning
confidence: 97%